La letteratura popolare in Italia al bivio tra riforma e controriforma - Bronzini, Giovanni Battista (Traditiones (Ljubljana), 1999)
The article is based on the reflections of Antonio Gramsci (l891-1937) about the common points and differences between the religion practiced by the people and the religion of the church. In his article the author illustrates how contrasts between Reformation and Conter-Reformation are reflected in the elements of folk literature. He discusses two thematically different, yet structurally analogous ways of forming folk texts
Keywords: ethnology; etnologija; ljudsko slovstvo; oral literature